ANALISIS SOAL TES KOMPETENSI KEBAHASAAN PADA PENILAIAN TENGAH SEMESTER BAHASA ARAB SEKOLAH MENENGAH PERTAMA - Ahmad, Habibah; Auliya, Afra Nada (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The knowledge aspects of Arabic language by an Arabic learner have a positive correlation with their Arabic language skills. A competent person of these aspects of Arabic language can be tested through language competence test which includes grammatical test and vocabulary test. The purpose of this research is to find out the characteristics of language tests on midterm assessment questions (PTS) Arabic subjects of grade IX students of Junior High School (SMP) Innovative School Cianjur for the 2023-2024 academic year. This research is a descriptive qualitative type, with document review as a data collection technique, then the data obtained will be analyzed through the stages of reduction, presentation, and verification. The results showed that: 1) The form of Arabic competency test on PTS questions for grade IX students of SMP Innovative School Cianjur for the 2023-2024 academic year, includes sentence structure test, morphological structure test without text, vocabulary comprehension test in text and without text, and vocabulary storage test in text, with multiple-choice question forms and essay. 2) The Arabic language competency test on PTS questions for grade IX students of SMP Innovative School Cianjur for the 2023-2024 academic year is quite good when viewed from the contextuality of the content because it has minimized discrete tests even though it is still in simple text and question form.